2014
DOI: 10.1007/s00128-014-1213-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Antioxidant Responses in Pale Chub (Zacco platypus) Exposed to Copper and Benzo[a]pyrene

Abstract: In this study, antioxidant responses including lipid peroxidation (LPO), superoxide dismutase (SOD), catalase (CAT) and glutathione S-transferase (GST), were evaluated in the liver, gill and muscle tissues of pale chub (Zacco platypus) exposed to copper (Cu) and benzo[a]pyrene (BaP). Cu exposure induced significant antioxidant responses in Z. platypus, particularly in the liver, whereas BaP exposure had a negligible effect. Following Cu exposure, both SOD and CAT activity increased in a concentration-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies on fishes also found that antioxidant responses in the liver are more responsive to pollution than in other organs, as described in a study on Zacco platypus after waterborne exposure to Cu (Kim et al 2014), as well as in a study on O. niloticus, whose liver presented a higher sensitivity than its kidney (Atli and Canli 2010). The liver is a key organ in evaluating the effects of pollutants in fish (Bernet et al 1999).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies on fishes also found that antioxidant responses in the liver are more responsive to pollution than in other organs, as described in a study on Zacco platypus after waterborne exposure to Cu (Kim et al 2014), as well as in a study on O. niloticus, whose liver presented a higher sensitivity than its kidney (Atli and Canli 2010). The liver is a key organ in evaluating the effects of pollutants in fish (Bernet et al 1999).…”
Section: Discussionmentioning
confidence: 86%
“…The antioxidant enzymes have been shown to work in a cooperative or synergistic manner to protect against oxidative stress and tissue‐specific damage. These enzyme systems have been proposed as biomarkers of ROS in mediating contaminant exposure and as a potential tool in environmental risk assessment (Ibrahem, Khairy, & Ibrahim, ; Kim et al, ; Kohen & Nyska, ).The present study revealed that SOD activity and GSH content in the kidneys of Nile tilapia fish exposed to crude oil were reduced significantly ( p ≤ .05) in group II intoxicated with used engine oil. These results are in agreement with results reported by Kayode Chidimma and Alwell ().…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that pollutants such as pharmaceuticals and personal care products and other toxic substances in the environment are able to induce the intercellular overproduction of ROS, thus damaging plant cells (Kim et al 2014;Liu et al 2014). MDA formation is considered to be a general indicator of lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%